SISTEM INFORMASI PEMBELAJARAN ONLINE BERBASIS WEB DI SMK N 1 DEPOK - Fahri Rusliyadi; Linda Sari Dewi (Jurnal Informatika Teknologi dan Sains, 2022)
Although the use of Google Classroom has more or less facilitated learning activities between students and teachers at SMK N 1 Depok, there are still shortcomings and limitations. Attendance performed manually is ineffective and prone to errors during the recap process. Information and announcements related to learning only done through WhatsApp Groups are also not effective because they are often missed by students. Therefore, online learning media is needed using e-learning which is equipped with attendance and announcement features so that teaching and learning activities can be carried out more effectively and efficiently. This e-learning is made in the form of a website using the waterfall method, whose system development uses the PHP programming language and MySQL database. Web development also uses the Laravel and Vue.js frameworks to make the process faster and easier. With this e-learning, teaching and learning activities can be easier because it can be accessed at any time and makes it easier for students and teachers to see announcements and the attendance process and attendance recap no longer need to be done manually.